Maintaining Online Media Amidst the Aggressive Determinism of Social Media - Fianto, Latif; Ghofur, M. Abdul; Fauzuna, Hafidlatul; Kusufa, Fendiyatmi (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2024)
Online media is the new face of the existence of mass media, which enjoyed its heyday as a medium of information for society. However, this heyday did not last long, because social media is not only a threat but has also shifted the position of mass media as an information medium. This research aims to determine the extent of efforts made by online media to maintain its existence amidst the aggressive determinism of social media. This research was carried out using a qualitative approach with the method used being a case study. The research was conducted on the online media Jatimtimes.com and Tugumalang.id. The research results show that Jatimtimes.com specifically targets young people as an audience segmentation because young people are very familiar with and cannot even be separated from the existence of technology and social media. This encourages Jatimtimes.com to present news that suits the needs of young people as their main audience. Meanwhile, Tugumalang.id places more emphasis on writing news straightforwardly and clearly as it should be presented in writing journalistic works. Writing news in straightforward and clear language will be easier for readers to understand.